The recovery of waste heat of flue gas from gas boilers. (3rd April 2017) - Zhao, Xiling; Fu, Lin; Sun, Tao; Wang, Jing Yi; Wang, Xiao Yin
Abstract : There is a large amount of water vapor with substantial latent heat in the flue gas from natural gas boilers. The energy efficiency could be improved significantly by the recovery of the waste latent heat. This article analyzes the potential of waste heat recovery, proposes the problems of traditional district heating systems, and develops a new process flow, which could reduce the outlet temperature of the flue gas to about 20°C. An experiment of this process has been conducted, as well as the analysis of energy consumption and economic performance. The reduction rate of energy consumption is 10% to 15%, and the payback year is less than 3 years.